PH Dependent Optical Switching and Fluorescence Modulation of Molybdenum Sulfide Quantum Dots. Issue 9 (29th March 2017) - Mishra, Himanshu; Umrao, Sima; Singh, Jai; Srivastava, Rajesh Kumar; Ali, Rashid; Misra, Arvind; Srivastava, Anchal
Abstract : Investigations on fluorescent molecules with fluorescence switching behavior as function of pH, temperature, ion concentration, etc. is highly desirable in the field of sensor device fabrication. In this study, the authors report an easy and eco‐friendly hydrothermal route for the synthesis of pH dependent fluorescent MoS2 quantum dots (MoS2 ‐QDs). The average size of the synthesized QDs is found to be ≈7 nm which was confirmed with transmission electron microscopy and atomic force microscopy. These MoS2 ‐QDs show the pH dependent fluorescence switching behavior. Under pH ≈ 1 the fluorescence intensity of the MoS2 ‐QDs is quenched while it shows ≈200 times enhancement under pH ≈ 13. This florescence ON/OFF switching is mainly due to the surface adsorbed functional groups (NH2, SO4 2−, OH −, etc.) and is a combined effect viz. protonation–deprotonation process, acid etching, quantum confined Stark effect and particle agglomeration. A plausible mechanism for this pH dependent ON/OFF switching behavior is also discussed in this study. The band gap calculation under different pH environment is also in good agreement to the hypothesis. Abstract : In this study, MoS2 ‐quantum dots (QDs) are synthesized by using a facile and ecofriendly hydrothermal method using sodium molybdate andl ‐cysteine as starting materials. These MoS2 ‐QDs show pH dependent optical switching and fluorescence modulation behavior.